Age and hemispheric differences in transcallosal inhibition between motor cortices: an ispsilateral silent period study - Davidson, Travis; Tremblay, François (Université d'Ottawa | University of Ottawa, 2013)
In this study, we investigated age and hemispheric differences in transcallosal inhibition (TCI) in the context of active contraction using the ipsilateral silent period (iSP). We also examined whether age-related changes in TCI would be related to corresponding changes in manual performance with age. Participants consisted of right-handed individuals from two age groups (young adults, n=13; seniors, n=17). The iSP was measured for each hemisphere using suprathreshold TMS pulses delivered over the primary motor cortex ipsilateral to the maximally contracting hand while the homologue muscles of the opposite hand were lightly contracting (~15% of the maximum). Manual performance was assessed bilaterally for both grip strength and fine dexterity.